2018
DOI: 10.1021/acs.jmedchem.7b01891
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibition of MicroRNA miR-21 Rescues Chemosensitivity of Renal-Cell Carcinoma to Topotecan

Abstract: Chemical probes of microRNA (miRNA) function are potential tools for understanding miRNA biology that also provide new approaches for discovering therapeutics for miRNA-associated diseases. MicroRNA-21 (miR-21) is an oncogenic miRNA that is overexpressed in most cancers and has been strongly associated with driving chemoresistance in cancers such as renal cell carcinoma (RCC). Using a cell-based luciferase reporter assay to screen small molecules, we identified a novel inhibitor of miR-21 function. Following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 63 publications
(101 reference statements)
0
32
0
Order By: Relevance
“…MicroRNAs (miRNAs) are master gene regulators that may silence genes at the post-transcriptional level via transcript degradation or translational repression. miRNAs are extensively implicated in fundamental biological processes and aberrant microRNA profiles have been reported in various cancers including RCC [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are master gene regulators that may silence genes at the post-transcriptional level via transcript degradation or translational repression. miRNAs are extensively implicated in fundamental biological processes and aberrant microRNA profiles have been reported in various cancers including RCC [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In CC, miR-21 is demonstrated to participate in DDP plus PTX resistance and indicates a poor prognosis [146]. What's more, the silencing of miR-21 can rescue the expression of tumor suppressor proteins and reverse topotecan resistance in renal cell carcinoma (RCC) [147]. Additionally, in papillary thyroid carcinoma (PTC), upregulation of miR-206 contributes to euthyrox resistance by blocking the p38 and JNK signaling pathway via targeting MAP 4 K3 [135].…”
Section: Other Cancersmentioning
confidence: 99%
“…Experiments that assess off-target interactions and RNA selectivity are clearly important when it comes to testing novel RNA-binders in vitro and in vivo (Naro et al 2018;Zhang et al 2020;Costales et al 2017;Abulwerdi et al 2019;Donlic et al 2018). However, our survey of the HIV-1 TAR literature ( Supplementary Table S2) revealed that these controls are not always performed (Gelus et al 1999;He et al 2005;Hwang et al 2003).…”
Section: Rnasmentioning
confidence: 99%
“…Such compounds with demonstrated cellular activity have been enumerated in the R-BIND database (Morgan et al 2019). Some of these compounds have been shown to bind specific RNAs and inhibit their cellular activities with well-validated selectivity (Costales et al 2017(Costales et al , 2019Zhang et al 2020;Shi et al 2019;Haga et al 2015;Naro et al 2018).…”
Section: Introductionmentioning
confidence: 99%